2022
DOI: 10.1088/1748-0221/17/09/c09006
|View full text |Cite
|
Sign up to set email alerts
|

Testbeam performance results of bent ALPIDE monolithic active pixel sensors in view of the ALICE Inner Tracking System 3

Abstract: The ALICE Inner Tracking System has been recently upgraded to a full silicon detector consisting entirely of monolithic active pixel sensors, arranged in seven concentric layers around the LHC beam pipe. Further ahead, during the LHC Long Shutdown 3, the ALICE collaboration is planning to replace the three innermost layers of this new ITS with a novel vertex detector. The proposed design features wafer-scale, ultra-thin, truly cylindrical MAPS. The new sensors will be thinned down to 20–40 µm, featuring a mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…11 right) [38], forming a 10 m 2 active detection area with a total of 12.5 ×10 9 pixels. ALPIDE is fabricated using the TowerJazz 180 nm quadra-well HR CMOS process ( > 1 kΩ cm), and features 512 × 1024 pixels with the pitch of 28 μm , providing a sensitive area of 30 mm × 13.8 mm [41]. Its pixel includes an octagon collection diode which achieves nearly 100% CCE [36]; Right: MIMOSA28 on its PCB.…”
Section: Silicon Pixel Detectormentioning
confidence: 99%
“…11 right) [38], forming a 10 m 2 active detection area with a total of 12.5 ×10 9 pixels. ALPIDE is fabricated using the TowerJazz 180 nm quadra-well HR CMOS process ( > 1 kΩ cm), and features 512 × 1024 pixels with the pitch of 28 μm , providing a sensitive area of 30 mm × 13.8 mm [41]. Its pixel includes an octagon collection diode which achieves nearly 100% CCE [36]; Right: MIMOSA28 on its PCB.…”
Section: Silicon Pixel Detectormentioning
confidence: 99%
“…The ITS3 design [1] foresees the replacement of the three innermost layers of the current ALICE tracker (ITS2) with wafer-scale stitched MAPS (65 nm) bent to cylindrical shapes. Multiple (beam) tests [2] with the existing ITS2 MAPS (=ALPIDE chip, 180 nm) showed that the ALPIDE retains functionality and performance when operated in a bent state.…”
Section: Introductionmentioning
confidence: 99%